2018
DOI: 10.3201/eid2404.172124
|View full text |Cite
|
Sign up to set email alerts
|

Novel Highly Pathogenic Avian Influenza A(H5N6) Virus in the Netherlands, December 2017

Abstract: A novel highly pathogenic avian influenza A(H5N6) virus affecting wild birds and commercial poultry was detected in the Netherlands in December 2017. Phylogenetic analysis demonstrated that the virus is a reassortant of H5N8 clade 2.3.4.4 viruses and not related to the Asian H5N6 viruses that caused human infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
78
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 10 publications
5
78
0
Order By: Relevance
“…In December 2017, the Netherlands was first to report HPAI H5N6 in Europe (Beerens et al., ). Later in 2017–2018, the H5N6 virus was also detected in wild birds in several other European countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In December 2017, the Netherlands was first to report HPAI H5N6 in Europe (Beerens et al., ). Later in 2017–2018, the H5N6 virus was also detected in wild birds in several other European countries.…”
Section: Discussionmentioning
confidence: 99%
“…H5N6 viruses were detected in 15 dead wild birds tested in the passive wild bird surveillance programme. We previously showed that this virus is a novel reassortant of the HPAI H5N8 clade 2.3.4.4 group B virus that obtained new PB2 and NA segments derived from Eurasian LPAI viruses (Beerens et al., ). Phylogenetic analysis demonstrated that the virus is not related to the H5N6 virus detected in Greece in February 2017, as it carries genetically different PA and PB2 gene segments.…”
Section: Discussionmentioning
confidence: 99%
“…Clade 2.3.4.4B H5N6 viruses were detected in the Netherlands, South Korea and China in 2017–2018. The H5N6 virus detected in the Netherlands was a reassortant of H5N8 Clade 2.3.4.4B viruses that obtained novel PB2 and NA segments derived from Eurasian LPAIVs (Beerens, ), and the viruses isolated in South Korea were obtained from a reassortment that occurred between Clade 2.3.4.4B H5N8 viruses and Eurasian LPAIVs circulating in wild birds (Kim, ). The virus isolated in China was a reassortant of Clade 2.3.4.4B H5N8 viruses with novel NA segments derived from Asian LPAIVs and was genetically similar to H5N6 HPAIVs identified from Japan (Liu, ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the phylogenetic analysis of the PB2 and M genes, the novel H5N6 HPAIVs grouped into Clade 2.3.4.4B and belonged to three clusters designated Cluster I, Cluster II and Cluster III. The novel H5N6 HPAIVs were successively isolated from domestic poultry and wild birds in Japan, China (Cluster I), the Netherlands (Cluster I and III), Korea, Germany and England (Cluster I) during the 2017–2018 winter (Beerens, ; Kim, ; Liu, ). In addition to the H5N6 HPAIVs, one H5N6 LPAIV, which was also detected in Ningxia, China, was a reassortant influenza virus carrying the HA and NA gene segments originating from LPAIVs and all six internal gene segments from H5N8 HPAIVs and is classified as Cluster IV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation